An Analysis of Cooperative Principles on Asumsi.co's Interviews on Russia-Ukraine War Issue - Rizqy, Hafiz Alfandy; Revita, Ike; Aslinda, Aslinda (English Department, Faculty of Humanities, Andalas University, 2023)
Cooperative Principle is one of the pragmatics disciplines that should be known by everyone to conduct effective communication, especially diplomats. This research studied the utterances which were uttered by two Russian diplomats who are actively working at the Russian Embassy in Indonesia, Denis Tetyushin and Lyudmila Vorobyova in their interviews with Asumsi.co. The objectives of this research were to identify the maxims of cooperative principle which are produced by the interviewees in the Asumsi.co interviews, to figure out the types of maxims disobedience which are produced by the interviewees, and to recognise the motives behind the interviewees obeying and disobeying the maxims. This study was conducted with a qualitative approach assisted by a statistical descriptive method to see the distribution of the obedience and disobedience utterances. The result of the research revealed 47 data obey and disobey the maxim of cooperative principles. The most obeyed maxim was the maxim of manner, followed by the maxim of quantity, the maxim of quality, and there was no utterance which followed the maxim of relevance rule.